2013
DOI: 10.1021/nl400921p
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Embedded Metal Oxide Nanoparticles in Vertically Aligned Carbon Nanotube Forests as Pseudocapacitor Electrodes for Enhanced Energy Storage

Abstract: Carbon nanotube (CNT) forests were grown directly on a silicon substrate using a Fe/Al/Mo stacking layer which functioned as both the catalyst material and subsequently a conductive current collecting layer in pseudocapacitor applications. A vacuum-assisted, in situ electrodeposition process has been used to achieve the three-dimensional functionalization of CNT forests with inserted nickel nanoparticles as pseudocapacitor electrodes. Experimental results have shown the measured specific capacitance of 1.26 F/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 25 publications
0
92
0
Order By: Relevance
“…Most of the micro supercapacitor prototypes applied symmetric configuration and store energy with identical principle in two electrodes. Though developed with various types of materials including carbon with EDL capacitance [16e21], conducting polymer films with pseudocapacitance covered on 3D electrode architecture [22,23], and composite electrode materials incorporating the synergistic effect of both types [24], the energy density of the micro supercapacitors is still not satisfying.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the micro supercapacitor prototypes applied symmetric configuration and store energy with identical principle in two electrodes. Though developed with various types of materials including carbon with EDL capacitance [16e21], conducting polymer films with pseudocapacitance covered on 3D electrode architecture [22,23], and composite electrode materials incorporating the synergistic effect of both types [24], the energy density of the micro supercapacitors is still not satisfying.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D graphene-CNT hybrids grown on nickel foam prepared by two-step CVD approach have been reported to exhibit a five-time-higher specific capacitance than CNT directly grown on inconel without graphene as the supporting substrate . Jiang et al (2013) prepared vertically aligned CNT forest with uniformly embedded nickel oxide nanoparticles, which delivered a 5.7 times higher specific capacitance (1.26 F cm −3 ) than pure CNT forest samples because of combination of both EDLC and pseduocapacitance ( Figure 6A). Niu et al (2014) reported a general strategy to prepare functional porous graphene hybrid architectures ( Figure 6B).…”
Section: Supercapacitorsmentioning
confidence: 99%
“…For instance Kurra et al employ CBD for the fabrication of micropseudocapacitors based on Ni(OH) 2 [14]. Liu et al use laser ablation in liquid (LAL) [15] and Jiang et al work with chemical vapor deposition (CVD) [16].…”
Section: Introductionmentioning
confidence: 99%